Efficacy of DAAs in the Treatment of Chronic HCV: Real-World Data from the Private Health-Care Sector of the Kingdom of Saudi Arabia - Almoutaz Hashim; Fadia Almahdi; Emad Aldin Albaba; Ohoud Barkia; Reem Alkasam; Asmaa Almahmoud; Ahmed Nabil; Ayman Alsulaimani; Mahmoud Mosli (Springer, 2020)
Background and Aim: The hepatitis C virus (HCV) is considered a global health challenge that requires urgent interventions for prevention and control. In this study, we aimed to evaluate the effectiveness of direct-acting antiviral agents (DAAs) for HCV-infected patients in the Kingdom of Saudi Arabia (KSA). Patients and Methods: In this retrospective cohort study, we ascertained data of patients treated with DAA-based regimens for chronic HCV in the private health-care sector hospitals of KSA between April 2015 and December 2017. Data regarding presence or absence of liver cirrhosis, virus genotype, quantitative HCV RNA test, fibrosis stage, and history of liver disease were included. The primary end point of the study was the overall cure rate, defined as the number of patients achieving sustained viral response (SVR) rate at least 12 weeks following completion of treatment, divided by the total number of patients included in the study. Results: A total of 262 patients fulfilled the study inclusion criteria. Adult patients were enrolled, of which 114 (44%) were females and 148 (56%) were males. About 105 of the patients (40%) were cirrhotic and 156 were treatment-naïve patients (60%), 84 patients were interferon (INF) experienced, and 22 patients had previously received new DAAs but failed to achieve SVR. The majority of patients received ledipasvir-sofosbuvir±RBV (57%) with SVR rate of approximately 97%. Conclusions: Our local real-world data indicate an overall HCV cure rate of 97% following treatment with DDA#x2019;s when prescribed in the private sector. This estimate is acquiescence with previously reported global cure rates.